Dynamic protein hydrogels with reversibly tunable stiffness regulate human lung fibroblast spreading reversibly. Issue 36 (15th April 2019) - Fu, Linglan; Haage, Amanda; Kong, Na; Tanentzapf, Guy; Li, Hongbin
Abstract : Fibroblast cells change their morphology reversibly in response to changes in protein hydrogel stiffness. Abstract : We report the engineering of a protein-based dynamic hydrogel that can be reversibly tuned between stiff and soft states via a redox reaction. When cultured on this hydrogel surface, human lung fibroblasts can dynamically and reversibly change their morphology in response to changes in hydrogel stiffness.